Pengolahan Pupuk Organik Dari Kotoran Kambing Dusun Sidomulyo, Desa Bangelan (Fakultas Teknik, Universitas Brawijaya, 2024)
The village of Bangelan holds significant potential in the livestock sector, particularly in goat farming. The Karya Mulya Farmer Group in Bangelan has been developing the Etawa breed of goats, known for their higher market value. Recognizing this potential, an innovation has emerged in processing goat manure into organic fertilizer, aiming to increase economic value and address environmental issues. This calls for an enhancement in utilizing goat resources and available land, as well as obtaining certification and distribution permits to improve the marketing of organic fertilizer products to a wider network.